Pelayanan Pemerintahan yang Bertanggung Jawab - Khairul Rahman (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2017)
The demands of services that priority the needs and demands of society will be difficult to be realized without the responbility of every apparatus government. The complain and even critics who often delivered about the low quality of public services at all levels has become the theme of daily conversation. All the evidence for the low quality of service received by society. The importance of building responsilbe government services because the society has the right to obtain services that prioritize the objectives development. This is based on the idea that the government is actually formed to provide services to the society and in fact the government to gain power in a democratic state is a mandate of society. The organizations of government are often referred to as ’society of services’ (public servant). In reality, not all officials government / administrators have realized the importance of service. The closer relationship between the service with the responsibility, the lack of undersatnding of the government apparatus for the importance of the service indicates the weakness of the responsibility of the apparatus government. The complaint from society of poor and disappointing services from the government and the flow of stories power abus. One of the causes, of all that is the lack of government responsibility to the society. An understanding of how to bulid government services is responsibility.